Progress in Martian seismology and temporal changes of Martian subsurface structure - Chuwen Xie; Zhikun Liu (地球与行星物理论评)
The exploration of the deep earth, deep sea, and deep space represents a major national science and technology strategy, and is also a cutting-edge research field in the world. Mars exploration falls within the realm of space exploration, whereas probing the interior of an exoplanet resembles the deep earth exploration. Consequently, exploring the subsurface structure of Mars can be considered a combination of deep space and deep earth exploration. It is of great significance to summarize and sort out the current research progress of Mars and find new research content. This article reviews the research progress of Mars seismology based on InSight data, including the new understanding of marsquakes properties and the investigation of Mars internal structure. The focus is on the background, principle and new progress of the studying on temporal velocity changes in Martian subsurface structure using the single seismic station onboard InSight and the observed diurnal and seasonal variation of seismic velocity are introduced. The influencing factors of Mars seismic velocity change are analyzed through relevant studies on the Earth and Moon. Problems and opportunities in the study of temporal changes in Martian media are also summarized. Finally, we prospect the research direction and development trend of time-varying monitoring of Martian media by using single-station method.